Santiago Pérez Triana (1898-1916) and the Pan-Americanization of the Monroe Doctrine (2018)
In recent years, historians have focused on efforts at the turn of the 20th century by Alejandro Álvarez, Luis María Drago, and Baltasar Brum (all Southern Cone diplomats) to foster continental cooperation by Pan-Americanizing the Monroe Doctrine. Overlooked in this endeavor are the remarkable activities of Colombian author, journalist, and diplomat, Santiago Pérez Triana. Using primary and secondary sources, this article analyzes Pérez Triana’s support of the Drago Doctrine at the 1907 Hague Convention, his speeches at the Pan-American Financial Conference in 1915, and his essays published in Hispania, a journal that he edited between 1912 and 1916, to show how he won the respect of American and European diplomats by emerging as an influential spokesman for Pan-Americanizing the Monroe Doctrine and for hemispheric unity.